LONG-TERM ENDOCRINE SEQUELAE AFTER COVID-19: CLINICAL INSIGHTS, DIGITAL HEALTH PERSPECTIVES AND PUBLIC HEALTH CHALLENGES - Katarzyna Bielawska (International Journal of Innovative Technologies in Social Science, 2025)
The COVID-19 pandemic has revealed that SARS-CoV-2 infection affects not only the respiratory system but also multiple endocrine organs, leading to a broad spectrum of long-term hormonal disturbances. This narrative review aims to summarize the current evidence on endocrine sequelae after COVID-19, emphasizing pathophysiological mechanisms, clinical manifestations, and implications for patient management. A structured literature search was conducted in PubMed, Scopus, Web of Science, and Google Scholar for studies published between January 2020 and October 2025 addressing endocrine or metabolic consequences of COVID-19.The reviewed data demonstrate that SARS-CoV-2 can impair the hypothalamic–pituitary–adrenal, thyroid, gonadal, pancreatic, and growth hormone axes through direct viral injury, immune-mediated inflammation, and chronic stress-axis dysregulation. Clinical consequences include secondary adrenal insufficiency, autoimmune thyroiditis, new-onset diabetes, hypogonadism, and menstrual disorders. While many abnormalities appear transient, a subset of patients develop persistent dysfunction requiring long-term follow-up.Tele-endocrinology and digital health solutions have emerged as valuable tools for monitoring endocrine recovery and improving access to care. However, significant research gaps remain, particularly regarding long-term prevalence, reversibility, and mechanisms of endocrine injury. Understanding and addressing these complications will require coordinated, multidisciplinary strategies that integrate clinical endocrinology, public health, and digital innovation.